2006
DOI: 10.1007/s11248-006-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Secretion of Recombinant Outer-surface Protein A from the Lyme Disease Agent, Borrelia burgdorferi, in Nicotiana tabacum Suspension Cells

Abstract: The ospA gene of Borrelia burgdorferi codes for an outer membrane lipoprotein, which is a major antigen of the Lyme disease agent. Recombinant OspA vaccines tested so far were expressed in Escherichia coli. In this study, we investigated the expression of a soluble OspA protein in Nicotiana tabacum suspension cells and evaluated the secretion of OspA driven by either its own bacterial signal peptide or a plant signal peptide fused to the amino-terminal cysteine of the mature form. In both cases, the signal pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The sequence encoding the HA ectodomain (codons 18–529) was amplified from this sequence using the primers HA-Chit (5′ TATCCTCGGCCGAAGATACCCTCTGCATTGG 3′) and HA-HFBIR (5′ CGAGTGAACCACCACCCTGATAGATCCTGGTACTC 3′). This was fused by overlap extension PCR to the signal peptide sequence (codons 1 to 21) of the Arabidopsis thaliana basic endochitinase (Accession number: P19171) amplified from pSK-chit-OspA [44] using the primers chitAgeI (5′AAC ACCGGT ATGAAGACTAATCTTTTTCTC 3′, AgeI site underlined) and Chit-HA (5′ CCAATGCAGAGGGTATCTTCGGCCGAGGATAATGAT 3′). The resulting chit-HA fragment was cloned into the pGEM-T Easy vector and sequenced.…”
Section: Methodsmentioning
confidence: 99%
“…The sequence encoding the HA ectodomain (codons 18–529) was amplified from this sequence using the primers HA-Chit (5′ TATCCTCGGCCGAAGATACCCTCTGCATTGG 3′) and HA-HFBIR (5′ CGAGTGAACCACCACCCTGATAGATCCTGGTACTC 3′). This was fused by overlap extension PCR to the signal peptide sequence (codons 1 to 21) of the Arabidopsis thaliana basic endochitinase (Accession number: P19171) amplified from pSK-chit-OspA [44] using the primers chitAgeI (5′AAC ACCGGT ATGAAGACTAATCTTTTTCTC 3′, AgeI site underlined) and Chit-HA (5′ CCAATGCAGAGGGTATCTTCGGCCGAGGATAATGAT 3′). The resulting chit-HA fragment was cloned into the pGEM-T Easy vector and sequenced.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins in the cell extract (17 lg) or proteins in 100 ll of extracellular medium were precipitated using chloroform/methanol according to Wessel and Flugge (1984), then solubilized by boiling for 10 min in 16 ll of denaturation buffer (50 mM sodium citrate, pH 5.5 (HCl), 0.5% (w/v) SDS, 0.1 M b-mercaptoethanol) followed by addition of 1 ll of 10 mg/ml PMSF (in methanol) and 23 ll of citrate buffer [50 mM sodium citrate, pH 5.5 (HCl)] alone or containing 0.2 unit/ml of endoglycosidase H (ROCHE) as described by Navarre et al (2006). After incubation for 30 min at 37°C, the reaction was stopped by addition of 20 ll of 39 SDS loading buffer (see above).…”
Section: Endoglycosidase H Digestionmentioning
confidence: 99%
“…Analysis of the bacterial SS of OspA with TargetP [29] provided evidence that the genuine OspA SS could act as a presequence for targeting the protein to the apoplast. In fact, a previous study showed that OspA is secreted when expressed in Nicotiana tabacum suspension cells [30]. Hence, full-length OspA variants could not be detected in protoplasts.…”
Section: Production Of Ospa Variants Via a Transient Tobaccomosaic VImentioning
confidence: 95%